(untitled) (The Pakistan Development Review, 2003)
Raising the standards of literacy in the developing world has been a major goal of the less developed countries since most of them became independent in the process of decolonisation that followed World War II. The Human Development Report 2004, brought out by the United Nations Development Programme lists some major improvements in increasing literacy levels of a number of countries between the year 1990 and 2002. For example, low human development countries like Togo increased their adult literacy rates from 44.2 percent in 1990 to 59.6 percent in 2002. Congo saw an increase in its literacy rate for the same period from 67.1 percent to 82.8 percent. The rates for Uganda, Kenya, Yemen, and Nigeria are 56.1 percent and 68.9 percent, 70.8 percent and 84.3 percent, 32.7 percent and 49.0 percent, and 48.7 percent and 68.8 percent respectively. If one examines the breakdown by region, the least developed countries as a group saw an increase in their adult literacy rates from 43.0 percent to 52.5 percent, the Arab states from 50.8 percent to 63.3 percent, South Asia from 47.0 percent to 57.6 percent, Sub-Saharan Africa from 50.8 percent to 63.2 percent and East Asia and the Pacific from 79.8 percent to 90.3 percent. If we look at the increase in the levels of literacy from the perspective of medium human development and low human development, the figures are 71.8 percent and 80.4 percent, and 42.5 percent and 54.3 percent, respectively.